The Law of Wiping the Jaurab and Khuf Using the Qiyas Method from the Perspective of Islamic Jurisprudence - Lafifah; Najwa Khalilah Harahap; Muhammad Zakaria; Bagus Hamdani Parapat; Arswendo Tyo Maulana (ISNU Nine-Star Multidisciplinary Journal, 2024)
This study aims to analyze the metaphorical method between wiping socks and wiping khuf from the perspective of Islamic jurisprudence of worship. This study is included in the type of qualitative research using the library research method, which is a study conducted by collecting data from books and literature from previous studies, or research conducted by collecting data from searches or other writings both from scientific articles, primary data sources and secondary data sources, and other literature related to the metaphorical method. The results of the study found are as follows. First, the type of metaphor used in determining the law of wiping jaurab which is likened to the law of wiping khuf is the metaphor of 'illah by equating the legal ilat of far' with its aṣl, where the determination of the legal ilat uses the istinbāt method by means of munāsabah. Second, the figurative method used in determining the law on whether it is permissible to wipe socks in wudu as a substitute for washing the feet which is ascribed to the law of wiping the khuf is valid because it fulfills the pillars of kias and also complies with the requirements of each pillar.